Exploring the Impact of the Gut Microbiota/REV-ERBα/NF-κB Axis on the Circadian Rhythmicity of Gout Flares from a Chronobiological Perspective - Wang H; Liu M; Xie C; Zhao L; Wang H (Journal of Inflammation Research)
Hao Wang, Mingxuan Liu, Cunxiang Xie, Luming Zhao, Hailong Wang Department of Rheumatology and Immunology, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of ChinaCorrespondence: Hailong Wang, Department of Rheumatology and Immunology, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, 100700, People’s Republic of China, Email wanghailong@bucm.edu.cnIntroduction: Gout is an inflammatory arthritis caused by the deposition of monosodium urate crystals in joints, severely affecting patients’ health. However, the management of gout remains suboptimal. Current clinical treatments primarily focus on anti-inflammatory and urate-lowering medications, which are associated with potential toxicities and other limitations. Chronotherapy, based on chronobiology, has gradually demonstrated unique advantages in the treatment of various inflammatory diseases and holds promise as a safer and more effective new strategy for treating gout.Objective: This article aims to explore the biological mechanisms underlying the circadian rhythmicity of gout flares and the potential role of chronobiology-based therapeutic approaches in the treatment of gout.Methods: The referenced research articles were sourced from major scientific databases, including Google Scholar, PubMed, and Web of Science. The search strategy employed keywords such as “Gout”, “Circadian rhythm”, and “Chronobiology”.Results: As the core inflammatory signaling pathway in gout, the NF-κB signaling pathway exhibits strong circadian rhythmicity under the regulation of circadian clock genes such as REV-ERBα. The gut microbiota may induce circadian oscillations in serum uric acid(UA) levels and trigger the rhythmic occurrence of gout flares by influencing the expression of REV-ERBα, rhythmically activating the NF-κB inflammatory signaling pathway, and altering the abundance. Therefore, the gut microbiota/REV-ERBα/NF-κB axis may be the potential biological mechanism underlying the circadian rhythmicity of gout flares.Conclusion: From the perspective of chronobiology, a chronobiology-based therapeutic approach targeting the gut microbiota/REV-ERBα/NF-κB axis—such as adjusting medication timing, dietary interventions to modulate the gut microbiota, and targeted pharmacological agents—holds promise as a novel clinical strategy for treating gout and has potential clinical value. However, the conclusions drawn in this paper lack scientific experimental and clinical validation. Therefore, exploring this therapeutic approach represent a key and promising direction for treating gout.Keywords: gout flare, circadian rhythm, chronobiology, gut microbiota, REV-ERBα, NF-κB